ECG-based 4D-dose reconstruction of cardiac arrhythmia ablation with carbon ion beams: application in a porcine model - Richter, Daniel; Lehmann, H. Immo; Eichhorn, Anna; Constantinescu, Anna M.; Kaderka, Robert; Prall, Matthias; Lugenbiel, Patrick; Takami, Mitsuru; Thomas, Dierk; Bert, Christoph; Durante, Marco; Packer, Douglas L.; et al. (Physics in Medicine and Biology, 2017)
Noninvasive ablation of cardiac arrhythmia by scanned particle radiotherapy is highly promising, but especially challenging due to cardiac and respiratory motion. Irradiations for catheter-free ablation in intact pigs were carried out at the GSI Helmholtz Center in Darmstadt using scanned carbon ions. Here, we present real-time electrocardiogram (ECG) data to estimate time-resolved (4D) delivered dose. For 11 animals, surface ECGs and temporal structure of beam delivery were acquired during irradiation. R waves were automatically detected from surface ECGs. Pre-treatment ECG-triggered 4D-CT phases were synchronized to the R-R interval. 4D-dose calculation was performed using GSI's in-house 4D treatment planning system. Resulting dose distributions were assessed with respect to coverage (D95 and V95), heterogeneity (HI = D5-D95) and normal tissue exposure. Final results shown here were performed offline, but first calculations were started shortly after irradiation The D95 for TV and PTV was above 95% for 10 and 8 out of 11 animals, respectively. HI was reduced for PTV versus TV volumes, especially for some of the animals targeted at the atrioventricular junction, indicating residual interplay effects due to cardiac motion. Risk structure exposure was comparable to static and 4D treatment planning simulations. ECG-based 4D-dose reconstruction is technically feasible in a patient treatment-like setting. Further development of the presented approach, such as real-time dose calculation, may contribute to safe, successful treatments using scanned ion beams for cardiac arrhythmia ablation.
EVALuna2:36481